1977
DOI: 10.1111/j.1600-0447.1977.tb03561.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment of Huntington's chorea

Abstract: The therapeutic effect of lithium in Huntington's chorea was tested in six patients through a double-blind cross-over comparison of lithium and placebo, each administered for 6 weeks. Four of the patients received neuroleptic drugs at the same time. Lithium and placebo periods did not differ as regards motor skills, hyperkinesias, or total ward situation, all rated quantitatively with the use of scales. Lithium does not seem to be of therapeutic value in Huntington's chorea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Combined therapy with lithium and neuroleptics also proved beneficial in several HD patients (Anden et al, 1973; Leonard et al, 1974; 1975; Manyam & Bravo-Fernandez, 1973; Schenk & Leijnse-Ybema, 1974). However, some other reports showed that lithium exerted no beneficial effects in HD patients (Aminoff & Marshall, 1974; Vestergaard et al, 1977). In some instances, lithium treatment even worsened motor and cognitive performance, particularly when used as the sole therapeutic agent (Carman et al, 1974; Leonard et al, 1974).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 92%
“…Combined therapy with lithium and neuroleptics also proved beneficial in several HD patients (Anden et al, 1973; Leonard et al, 1974; 1975; Manyam & Bravo-Fernandez, 1973; Schenk & Leijnse-Ybema, 1974). However, some other reports showed that lithium exerted no beneficial effects in HD patients (Aminoff & Marshall, 1974; Vestergaard et al, 1977). In some instances, lithium treatment even worsened motor and cognitive performance, particularly when used as the sole therapeutic agent (Carman et al, 1974; Leonard et al, 1974).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 92%
“…These trials included only small numbers of patients (9, 6, and 6) for very short time periods (6–12 weeks). In each case, the findings indicated that there were no improvements in involuntary movements, hyperkinesia, motor skills, or in the ability to perform everyday tasks, leading to the conclusion that lithium did not appear to be of therapeutic value in HD (Aminoff and Marshall, 1974 ; Leonard et al, 1975 ; Vestergaard et al, 1977 ). Since the 1970s, there have not been any reported human clinical trials utilizing lithium for treatment of HD; however, there has been a recent off-label use of lithium in a case study involving three individuals.…”
Section: Lithium Effects In Other Neurodegenerative Diseasesmentioning
confidence: 99%
“…Taken together, these clinical studies support lithium's potential to improve the psychiatric and possibly motor symptoms of HD. Despite these findings, two placebo-controlled, blind clinical trials reported that lithium was ineffective in the treatment of choreiform movements 156 , 158 . However, in both studies, sample size was small, the duration of lithium treatment was relatively short, and standardized measures were not used to report mood changes.…”
Section: Clinical Trials Of Lithium and Vpa In Hdmentioning
confidence: 99%